WTAP modulates macrophage polarization in rheumatoid arthritis by targeting exosomal circ-CBLB via m6A modification - Yan, Dawei; Wan, Lei (Frontiers in Immunology, 2025)
IntroductionInteractions between fibroblast-like synoviocytes (FLSs) and macrophages are pivotal in the pathogenesis of rheumatoid arthritis (RA). Exosomal circular RNAs (circRNAs) are key players in the communication between RA-FLSs and macrophages, yet their specific roles in RA pathogenesis remain undefined.This study aims to investigate the specific regulatory mechanisms of exosomal circRNAs in RA and their function in macrophage polarization through in vitro experiments.MethodsRA-FLSs were stimulated with TNF-α to mimic the enhanced inflammatory microenvironment in RA, while exosome secretion was inhibited using GW4869. WTAP expression was modulated via transfection (overexpression or knockdown), and m⁶A modification levels were analyzed using MeRIP-qPCR. Protein-RNA interactions, macrophage polarization, and cytokine profiles were evaluated through RNA pull-down assays, RIP-qPCR, flow cytometry, and ELISA, respectively.ResultsIn the enhanced inflammatory microenvironment of RA, circ-CBLB expression was observed to be significantly downregulated. Further functional validation showed that inhibition of exosome secretion intensified macrophage polarization toward the pro-inflammatory M1 phenotype. Screening of m6A modification-related enzymes combined with RNA pull-down and RIP-qPCR assays exhibited that WTAP protein directly bound to circ-CBLB and accelerated circ-CBLB degradation by enhancing its m6A modification levels. Functional experiments demonstrated that WTAP overexpression decreased exosomal circ-CBLB levels and promoted macrophage polarization toward the pro-inflammatory M1 phenotype, which was reversed by m6A modification site mutation.DiscussionThis study reveals a novel mechanism that exosomal circ-CBLB secreted from RA-FLSs affects macrophage polarization under the regulation of WTAP-mediated m6A modification, underscoring the potential of interventions targeting the WTAP-circ-CBLB axis in RA treatment.